How Turbidity Mediates the Combined Effects of Nutrient Enrichment and Herbivory on Seagrass Ecosystems - Wang, Xinyan; Bai, Junhong; Yan, Jiaguo; Cui, Baoshan; Shao, Dongdong (Frontiers in Marine Science, 2022)
While nutrient enrichment and herbivory have been well recognized as the main driving factors of seagrass meadow fragmentation and degradation, there is limited understanding of how their relative importance shifts across large spatial scales where environmental factors such as turbidity can vary. In this study, a field control experiment was conducted in two Zostera japonica meadows distributed on the two banks of the Yellow River Estuary with different turbidity, to investigate the combined effects of nutrient enrichment and herbivory on seagrass and macroalgae. Our results showed that turbidity had the mediating force of shifting the relative importance of nutrient enrichment and herbivory to seagrass and macroalgae. While herbivory played a vital role in maintaining the balance between the two primary producers in a turbid environment, nutrient enrichment tended to offset herbivory-induced biomass loss by promoting seagrass growth in a less turbid system. Additionally, two potential mechanisms that might regulate the responses of seagrasses and macroalgae to nutrient enrichment and herbivory under different turbidity are proposed. On the one hand, turbidity might mediate the feeding preference of herbivores. On the other hand, nutrient enrichment favors the growth of opportunistic macroalgae over seagrass in turbid systems. Our study emphasizes the mediating force of turbidity on seagrass ecosystems, and provides references for the protection and restoration of seagrass meadows under multiple environmental stressors.